Are we ready to face the next wave of RSV surge after the COVID-19 Omicron pandemic in China? - Jiang, Wujun; Chen, Sainan; Lv, Meng; Zhang, Zhen; Wang, Zhihui; Shao, Xuejun; Hua, Shenghao; Hao, Chuangli; Wang, Yuqing (Frontiers in Cellular and Infection Microbiology, 2023)
China had its first wave of COVID-19 in 2020 and second wave of COVID-19 Omicron in 2022. The number of RSV cases decreased sharply in 2020 and 2022. Investigation of the resurge of RSV infections after the first wave of COVID-19 will guide us to take preventive actions before the resurge of RSV infections after the second wave of COVID-19 Omicron.We analysed epidemiological and clinical data of 59934 patients with lower respiratory tract infections (LRTI) from a prospective long-term cohort surveillance programme in Suzhou, China, collected from February 2016 to January 2022. The annual incidence of RSV infection in children aged <16 years in 2020 and 2021 was compared with the pre-pandemic years 2016 to 2019. We also compared the clinical characteristics, and RSV-related ICU admissions between pre-pandemic years and 2021.Among children with LRTI, the positive rate of RSV increased by 70.7% in 2021 compared to the average level in the pre-pandemic years. The RSV resurge in 2021 was most prominently in children aged 2-4 years (a significant rise compared with the expected value 149.1%; 95%CI, 67.7% to 378%, P < .01). The percentage of RSV-related ICU admissions decreased in 2021 (3.2% vs 6.7%, P<0.01). The death rate of RSV infections in 2021 was 0.2%, while that in prepandemic years was only 0.02%. RSV-associated death in immunocompetent children (complicated by necrotizing encephalitis) was firstly occurred in 2021.Our findings raise concerns for RSV control in Southeast China after the COVID-19 pandemic especially for children aged 2-4 years. Although ICU admissions were significantly reduced in this resurgence, we could not ignore the increase of RSV-associated death.